1962
DOI: 10.1086/127827
|View full text |Cite
|
Sign up to set email alerts
|

Activity in Comets at Large Heliocentric Distance

Abstract: Almost all that we know of the physical characteristics of comets has been learned from observing objects of moderately small perihelion distance. By far the greatest number of the objects represented in the catalogs of comets and comet orbits were discovered when they were relatively bright and therefore moderately close to the sun and to the earth. Details of structure in the head and tail can be studied only in the brighter comets. An

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Some of them also have tails of distinctive appearance at great distances from the Sun. The tails are featureless, without appreciable broadening with increasing distance from the nucleus, and the length of the tail is several minutes of an arc from the well-condensed head (Roemer 1962). Sekanina (1973Sekanina ( , 1975 was the first to interpret the orientation and general profile of the tails at large heliocentric distances using an approach developed by Finson & Probstein (1968).…”
Section: Resultsmentioning
confidence: 99%
“…Some of them also have tails of distinctive appearance at great distances from the Sun. The tails are featureless, without appreciable broadening with increasing distance from the nucleus, and the length of the tail is several minutes of an arc from the well-condensed head (Roemer 1962). Sekanina (1973Sekanina ( , 1975 was the first to interpret the orientation and general profile of the tails at large heliocentric distances using an approach developed by Finson & Probstein (1968).…”
Section: Resultsmentioning
confidence: 99%
“…As already pointed out by Roemer (1962), bright comets are the basic source of our knowledge about the physics of these celestial objects. The bright comets are mostly small objects observed at relatively short heliocentric distances during their favourable configuration relative to the Sun and the Earth.…”
Section: Introductionmentioning
confidence: 93%
“…2P/Encke's current aphelion and perihelion distances are 4.09 and 0.34 AU respectively. Early photographic studies of distant comets (i.e., comets at heliocentric distances greater than 3 AU) by Roemer (1962) showed that comets are often active at large distances from the sun. In her observations this activity was obvious in the form of spatially resolved comae and tails.…”
Section: Origin Of the Light Variations Near Aphelionmentioning
confidence: 99%